PENGARUH BUDAYA ORGANISASI DAN KECERDASAN EMOSIONAL TERHADAP MOTIVASI KERJA SERTA IMPLIKASINYA TERHADAP KINERJA PEGAWAI PADA SEKRETARIAT DEWAN PERWAKILAN RAKYAT (DPR) ACEH - Agustianur Agustianur; Nasir Nasir; Sulaiman Sulaiman (FEB - Unsyiah, 2018)
This study aims to determine the effect of organizational culture and emotional intelligence on work motivation and its implication on staff performance of Aceh Parliament Secretariat. Population of this study was overall employee who works on the Aceh Parliament Secretariat where were at about 255 employees. This study employed census method. The analytical method used is structural equation modeling (SEM). The results showed that organizational culture has no significant effect on work motivation; however, it effect on staff performance. Emotional intelligence significantly effect on both work motivation and staff performance at the Aceh Parliament Secretariat. Work motivation serves as a partial mediator between the effects of emotional intelligence on the staff performance of the Aceh Parliament Secretariat. The implications of this study, Secretariat of the Aceh Parliament need to improve intelligence capabilities of employees through technical assistance programs respectively